2020
DOI: 10.3390/buildings10060100
|View full text |Cite
|
Sign up to set email alerts
|

Profitability of Various Energy Supply Systems in Light of Their Different Energy Prices and Climate Conditions

Abstract: The majority of the single-family houses in Sweden are affected by deteriorations in building envelopes as well as heating, ventilation and air conditioning systems. These dwellings are, therefore, in need of extensive renovation, which provides an excellent opportunity to install renewable energy supply systems to reduce the total energy consumption. The high investment costs of the renewable energy supply systems were previously distinguished as the main barrier in the installation of these systems in Sweden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The review of the existing literature on the subject shows that there are previous studies that have evaluated the effect of climate variables on the financial profitability of energy sector companies (Errebai et al, 2022;Jalilzadehazhari et al, 2020). For example, some studies have evaluated the impact of temperature on wind and solar energy production.…”
Section: Introductionmentioning
confidence: 99%
“…The review of the existing literature on the subject shows that there are previous studies that have evaluated the effect of climate variables on the financial profitability of energy sector companies (Errebai et al, 2022;Jalilzadehazhari et al, 2020). For example, some studies have evaluated the impact of temperature on wind and solar energy production.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the profitability of the supply systems was analysed for four Swedish climate zones. The authors [10] concluded that the ground source heat pump system was the most profitable energy supply system, providing a lower PBP and a higher IRR for all the climate zones analysed, when compared with the other energy supply systems. Furthermore, the results reveal that increasing the energy price improved the profitability of the supply systems in all climate zones.…”
mentioning
confidence: 98%
“…Jalilzadehazhari et al [10] evaluated the profitability of a ground source heat pump, photovoltaic solar panels, and an integrated ground source heat pump with a photovoltaic system as three energy supply systems for a single-family house in Sweden. This study evaluates the profitability of the supply systems through the calculation of the payback period (PBP) and the internal rate of return (IRR) for these systems.…”
mentioning
confidence: 99%